A COMPILATION OF MOORED CURRENT METER OBSERVATIONS, VOLUME I. - Webster,Ferris; fofonoff,N. P. (1965)
Summaries of current measurements made with Richardson current meters at three moored stations in the Western North Atlantic are presented. Averaged quantities are presented in the form of computer-plotted curves. (Author)